The Android-based comic of Gajah Mungkur Dam: Improving mathematical representation and critical thinking abilities - Ahmad Priyadi; Heru Kuswanto (OmniaScience, 2023)
This research aims to: (1) develop a fesible Android-based comic media of Gajah Mungkur Dam, and (2) reveal the effectiveness of the developed comic media in improving mathematical representation and critical thinking abilities on the materials of work and energy. The research subjects are senior high school students, consisting of 262 students for the empirical testing, 36 students for the limited trial, and 72 students for the field trial. This research is research and development applying the 4D model, consisting the stages of definition, design, development, and dissemination. The research instrument includes a validation sheet, evaluation sheet, questionnaire, lesson plans, comic media, and mathematical representation and critical thinking ability tests. The developed comic media contains an introduction, comic's work and energy materials, users' manual, instructional video, and discussion column. The data analysis used the MANOVA test. The finding shows that the developed Android-based comic media of Gajah Mungkur Dam is feasible to use with the assessment score of 3.70 or in a very good category from the validator, and score of 3.10 or in a good category from students in the limited trial. The MANOVA test result shows that there is a significant difference between the control class and experimental class. The developed comic is effective in improving mathematical representation ability in the small effect category and in improving critical thinking skill in the medium effect category.